The Effect of Iron Giving on Hemoglobin Levels in Anemia Pregnant Women - Budi Santosa; Fitriani Nur Damayanti; Siti Nurjanah; Novita Nining Anggraini (Jurnal Kebidanan, 2022)
Anemia that occurs during pregnancy has become a global health problem. The amount of iron needed by pregnant women is much greater than that of non-pregnant women so pregnant women have a high risk of developing iron deficiency anemia. The method used in this study is a literature review study. The databases used in the source search are google scholar and Pubmed. The search for articles was carried out by collecting themes about the effect of iron administration on hemoglobin levels in anemic pregnant women. Pregnant women with anemia who consume iron show an increase in hemoglobin levels. Giving iron given for 90 days by consuming it once a day can increase hemoglobin levels by 1 g/dl.